Cerebrovascular disease at young age is related to mother’s health during the pregnancy—The Northern Finland Birth Cohort 1966 study ... - Rissanen, Ina; Geerlings, Mirjam I; Juvela, Seppo; Miettunen, Jouko; Paananen, Markus; Tetri, Sami (SAGE Journals, 2021)
Background and purposeFor prevention of cerebrovascular diseases at younger age, it is important to understand the risk factors occurring early in life. We investigated the relationship between mothers’ general health during pregnancy and the offspring’s risk of cerebrovascular disease in age of 15 to 52 years.MethodsWithin the population-based prospective Northern Finland Birth Cohort 1966, 11,926 persons were followed from antenatal period to 52 years of age. Information on their mother’s ill health conditions, i.e., hospitalizations, chronic diseases, medications, vitamin or iron supplement, fever, anemia, mood, and smoking was collected from 24th gestational week onwards. Ischemic and hemorrhagic cerebrovascular diseases of the offspring were identified from national registers in Finland. Cox proportional hazard models were used to estimate the association of mother’s health conditions with incidence of cerebrovascular disease in the offspring, with adjustments for potential confounders.ResultsDuring ...